OP12 Assessing models of ACP in primary care, the meta-LARC trial: part 6 developing patient-reported measures of goal concordant care. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Totten, A; Dorr, D; Michaels, L; Izumi, S
Abstract : Background and aims: Atient-reported goal concordance in serious illness care is an important primary outcome; however, no validated measure exists. As part of a trial of ACP, we sought to design and validate items for our trial that could form the basis for future measure development. Methods: To draft items we reviewed the literature for validated measures in goal attainment, shared decision-making, and concordance. We engaged stakeholders, including patients, providers, and researchers, to discuss what goal concordant care means, developed draft items, and reviewed these in two focus groups with patient and family advisors as well as with research teams from other funded advance care planning and palliative care projects. Results: Our draft instrument consists of 3 parts representing different approaches. The first part asks the patient whether their current care supports what is important to them and if any care received was unwanted. The second part is derived from the Life Preference Scale developed by Ariadne Labs. This asks patients to report on whether health care supports what they identify as their three most important goals. The third part includes process measures based on the content of serious illness conversations and asks patients if each step or activity happened. Conclusion: It is possible to develop a patient-reported measure of goal concordant care that has face validity based on measures of related or similar constructs and the input of a range of stakeholders. Validation and ongoing refinement of the measure will be conducted in parallel with the trial.